MEASUREMENT OF DISCHARGES TEMPERATURE IN LOW-TEMPERATURE ACOUSTOPLASMA - Bezhanyan, T.Zh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
The results of temperature measurements in the Argon discharge in plasma with acoustic perturbation are presented. Possibility of, as decreasing, so increasing of discharge temperature in several times is shown.